Politik Kebangsaan Kiai Pesantren (Studi Kepribadian dan Perilaku Politik K.H.R. Ach. Fawaid As?Ad Situbondo) - Arifin, Samsul; Wisri, Wisri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Political personality is the result of moving a private area into a public domain. Political behavior is also determined by the interaction and struggle of the politician's personality. Studies through the perspective of political psychology help us in understanding one's political behavior. This paper examines the personality and political behavior with the vision of the late K.H.R. Ach. Fawaid As'ad, one of the local political figures Pandhalungan from Islamic Boarding School Salafiyah Syafi'iyah Sukorejo Situbondo. The study used a qualitative approach of ethnographic-hermeneutic type. Data comes from documents and field notes. Result: Personality Kiai Fawaid, which has the character of patience and sincerity (dimension of neurotism); socializing, energetic, and dominant (extraversion dimensions); artistic, open to new ideas, and uphold the values of Islamic Boarding School (dimension of openness to experience), forgiving and altruism (dimension of agreeableness); discipline; organizational, and obedient rules (conscientiousness dimension). Kiai Fawaid makes political decisions-political parties or candidates in the election because of political considerations as a means of NU's struggle and for the benefit of the ummah. As for its implementation, it goes to political parties to improve the system and organize the nation starting from the district level. Kiai Fawaid's political behavior is related to the character of his personality, especially the dimensions of openness to experience and agreeableness